Westonci.ca connects you with experts who provide insightful answers to your questions. Join us today and start learning! Connect with a community of experts ready to help you find accurate solutions to your questions quickly and efficiently. Experience the ease of finding precise answers to your questions from a knowledgeable community of experts.
Sagot :
Answer:
Step-by-step explanation:
2x + 3y = 6
2x = 6-3y
x = (6-3y)/2
x - 3y = 9
(6-3y)/2 -3y = 9
(6-3y)/2 -6y/2 = 9
(6-9y)/2 = 9
6 - 9y = 9×2
-9y = 18-6
y = 12/-9
y = -4/3
2x + 3y = 6
2x + 3(-4/3) = 6
2x -4 = 6
2x = 6+4
2x = 10
x = 10/2
x = 5
Therefore x = 5 and y = (-4/3)
I used subsitution method
please click thanks and mark brainliest if you like :)
Answer:
x = 5; y = -4/3
Step-by-step explanation:
One equation has 3y. The other equation has -3y. Add the equations to eliminate y and solve for x.
2x + 3y = 6
(+) x - 3y = 9
---------------------
3x = 15
x = 5
2x + 3y = 6
2(5) + 3y = 6
3y + 10 = 6
3y = -4
y = -4/3
Answer: x = 5; y = -4/3
We hope our answers were useful. Return anytime for more information and answers to any other questions you have. We appreciate your time. Please come back anytime for the latest information and answers to your questions. Thank you for visiting Westonci.ca. Stay informed by coming back for more detailed answers.